Description of three new species and new distributional data for four species of Anagyrus (Hymenoptera: Encyrtidae) from China - Zu, Guo-Hao; Li, Cheng-De (Zootaxa, 2015)
Anagyrus brevifuniculus Zu & Li, sp. nov., A. maculistigmus Zu & Li, sp. nov. and A. pseudobicolor Zu & Li, sp. nov. are described; A. tricolor (Girault) is newly recorded from the Palaearctic region and A. matritensis (Mercet) from China. New distributional data for A. fusciventris (Girault) and A. jenniferae Noyes & Hayat are also provided.